1994
DOI: 10.1016/0735-1097(94)90495-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 100 mg of double-bolus alteplase in achieving complete perfusion in the treatment of acute myocardial infarction

Abstract: In 84 patients with acute myocardial infarction, administration of 100 mg of double-bolus (2 x 50 mg) alteplase, aspirin and heparin is associated with remarkably high early infarct-related coronary artery patency rates (TIMI flow grade 3) of 86% and 88%, respectively, at 60 and 90 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…In the Global Use of Strategies To Open Occluded Coronary Arteries IIb (GUSTO IIb) Angioplasty Substudy [36] , shock was not reduced in the angioplasty arm compared with Reteplase vs alteplase and cardiogenic shock 133 front-loaded, accelerated alteplase, despite the better patency achieved with angioplasty. Similarly, the double-bolus administration of alteplase, which reportedly is associated with a higher rate of TIMI 3 flow [37] , did not reduce the occurrence of cardiogenic shock [38] . These findings suggest that the incremental increase in the amount of myocardium that can be salvaged by improving the patency of the infarct-related arter relative to alteplase may be small.…”
Section: Thrombolytic Therapy and Prevention Of Shockmentioning
confidence: 99%
“…In the Global Use of Strategies To Open Occluded Coronary Arteries IIb (GUSTO IIb) Angioplasty Substudy [36] , shock was not reduced in the angioplasty arm compared with Reteplase vs alteplase and cardiogenic shock 133 front-loaded, accelerated alteplase, despite the better patency achieved with angioplasty. Similarly, the double-bolus administration of alteplase, which reportedly is associated with a higher rate of TIMI 3 flow [37] , did not reduce the occurrence of cardiogenic shock [38] . These findings suggest that the incremental increase in the amount of myocardium that can be salvaged by improving the patency of the infarct-related arter relative to alteplase may be small.…”
Section: Thrombolytic Therapy and Prevention Of Shockmentioning
confidence: 99%
“…The reduction in the 30-day mortality rate to 5.4 percent is proportional to the increase in the TIMI grade 3 flow rate at 90 minutes, from 54 percent with accelerated infusion (as in the GUSTO I trial) to 88 percent with double-bolus alteplase (as in the study by Purvis et al 10 ).…”
Section: End Points and Statistical Analysismentioning
confidence: 95%
“…8 In two early angiographic studies, high rates of patency were observed after double-bolus administration of alteplase, with no excess of bleeding complications. 9,10 In the largest of these studies, grade 3 flow rates (according to the Thrombolysis in Myocardial Infarction [TIMI] classification) were observed at 60 and 90 minutes in more than 85 percent of patients. 10 Thus, besides offering the advantage of ease of use, double-bolus alteplase might be at least as effective as the accelerated infusion as used in the GUSTO I study.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombolytic therapy with intravenous recom binant t-PA results in infarct-related artery patency in 70-85% of patients with acute myocardial infarction within 90 min of infusion, which is higher than that obtained with intravenous streptokinase or anistreplase [15,31]. An accelerated weight-adjusted dose of 1.25 mg/kg body weight of t-PA given over 90 min yields a high acute coro nary patency rate with a low reocclusion rate [32], Investi gational double bolus dose regimens with t-PA and a mutant recombinant plasminogen activator that has a prolonged half-life have also resulted in improved acute coronary patency rates [33,34], Unfortunately, even with accelerated t-PA, the GUSTO angiographic investigators found that while 81 % of the infarct-related arteries were patent at 90 min, only 54% had normal (TIMI 3) flow on angiography. The benefits of mortality reduction and improvement in ventricular function were restricted to the group of patients with normal flow on angiography at 90 min.…”
Section: Thrombolytic Therapymentioning
confidence: 96%